A coupling bimetallic Ni–La/MCM-41 catalyst enhanced by radio frequency (RF) plasma for dry reforming. (13th January 2022) - Xu, Junqiang; Tian, Huan; Chen, Kaipeng; Zhang, Qiang; Liu, Yalin; Cao, Wuyi; Guo, Fang
Abstract : Ni–La–Imp–P exhibited excellent stability and less carbon deposition (only 5.94%) after reacting at 700 °C for 20 h. Abstract : Controlling nickel particle size and inhibiting coke deposition on the supported catalyst are enormous challenges. To solve these problems, La-doped nickel-based catalysts using MCM-41 as the support were prepared via the radio frequency (RF) plasma-enhanced method. The Ni–La–Imp–P catalyst with a smaller nickel particle size, higher nickel dispersion, and a stronger metal–support interaction possessed more surface adsorbed oxygen than the conventional Ni–La–Imp catalyst, which was beneficial for the formation of more active Ni sites and enhanced the catalytic performance. In particular, the Ni–La–Imp–P catalyst showed excellent resistance to carbon deposition, and the carbon weight loss of the spent catalyst was only 5.94%, which was much less than those of conventional Ni–La–Imp (18.49%) and Ni–La–Sol (12.60%) catalysts. Nickel nanoparticles can effectively inhibit the growth of the carbon chain or the formation of the C–C bond to cover the surface site of Ni–La–Imp–P, thus reducing the formation of graphitic carbon and realizing the directional conversion of C (CH4 and CO2 ). Hence, the Ni–La–Imp–P catalyst activated by plasma proved to be a new method for enabling resistance to carbon deposition in dry reforming of methane.